Efficient access to some new pyrimidine derivatives and their antimicrobial evaluation. (10th August 2021) - El‐mahdy, Kamelia M.; Farouk, Osama
Abstract: 1‐[4‐(3‐Hydroxyphenyl)‐6‐methyl‐2‐thioxo‐1, 2, 3, 4‐tetrahydropyrimidin‐5‐yl]ethanone (1 ) was used as a precursor for heterocyclic synthesis. Condensation of compound 1 with monochloroacetic acid and benzaldehyde gave thiazolopyrimidine 2 which in turn underwent cyclization with malononitrile dimmer to afford malononitrile derivative 3 . Also, the reaction of compound 1 with benzaldehyde under a basic condition produced chalcone 4 . Chalcone 4 can be used as a key intermediate for further preparation of heterocyclic compounds. In addition, compound 1 was allowed to react with malononitrile dimmer and/or ethyl chloroacetate to give pyrimidines 8 and 9, respectively. Alkylation of compound 8 with ethyl chloroacetate afforded S ‐alkylated product 10 which was treated with hydrazine hydrate to yield the hydrazino derivative 11 . Alternative synthesis of compound 10 was taken place through reaction of compound 9 with malononitrile dimmer. The biological activity of the synthesized compounds was investigated. Compounds 1, 4, 5, and 8 recorded high activities against Gram positive bacteria ( S. aureus ). Structures of the new synthesized compounds were elucidated by elemental analysis and spectral data. Abstract : 1‐[4‐(3‐Hydroxyphenyl)‐6‐methyl‐2‐thioxo‐1, 2, 3, 4‐tetrahydropyrimidin‐5‐yl]ethanone(1 ) was used as a key intermediate for the synthesis of some novel pyrimidine derivatives. The biological activity of the synthesized compounds was investigated. Structures of the new synthesized compounds were elucidated by elemental analysis and spectral data.